SOCIAL MEDIA AUDIT, A NEW SCOPE FOR AUDITING - Eni Endaryati; Vivi Kumalasari Subroto (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2021)
The social media audit/assurance program aims to provide the management with the results of an assessment of the effectiveness of control over social media policies and processes in a company. Assurance program, this relates to audits that focus on operational effectiveness and how to monitor it and the effectiveness of strategies within the organization. Not only for the financial sector, audit activities can also be carried out for social media accounts. The term for this is a social media audit. The social media audit/assurance program aims to provide the management with the results of an assessment of the effectiveness of control over social media policies and processes in a company. The growing use of social media for entities/corporations can be used to create company publicity when someone finds an interesting story about the company in the online world. The existence of social media provides a new channel for companies to interact differently with consumers. If it is able to be utilized and managed properly, it can provide many positive impacts for the company. Social media can also be used as a media campaign that has a function as a strategic policy maker, which has various programs or policies that must be disseminated to the public. Keywords: social media audit, auditing, assurance program